The influences of work overload, role confict, work-family conflict, and career development towards job stress among employees in banking industry - Choong, Shi Yun; Goh, Yi Tong; Lee, Pei Ching; Sum, Wai Yan (2022)
The objective of this study was to examine the effects of workload, role conflict, work-family conflict, and career development on work stress among employees in the Malaysian banking industry. This study focused only on bank employees in Malacca, Perak, and Selangor. Our questionnaire was collected through Google form and 284 responses were successfully collected. All the data received from the respondents would be analysed using the Statistical Package for Social Sciences (SPSS). For the analysis of the data, reliability tests, Pearson Correlation Coefficients and Multiple Regression Analysis are used. In general, work overload and role conflict had a significant impact on employees' job stress, while work-to-family conflict, family-to-work conflict and career development did not have a significant impact on employees' job stress in the Malaysian banking industry. There are also some research implications, limitations and some recommendations pointed out in this study.